Solitary Schwannoma on the Hypothenar Region of the Hand: A Literature Review - G, Kastanis; P, Kapsetakis; G, Magarakis; M, Bachlitzanaki; C, Christoforidis; G, Kazamias; A, Pantouvaki (International Journal of Innovative Research in Medical Science, 2020)
Schwannomas or neurilemmomas are the most common benign tumors of the neural sheaths of the peripheral nerves. Incidence of these tumors in the hand accounts to 0.8-2%. The majority of them appear as an isolated grown mass along the route of the nerves. Peripheral nerves benign tumors present many difficulties concerning the clinical diagnosis and only histopathological evidence provides the final diagnosis. In this case study, we present a 45 year old man with a grown asymptomatic mass on the volar surface of right hand (hypothenar) remained for two years and impinging the skin of the hand only the last months. Initial MRI results diagnosed the mass as gaglion cyst. Histopathological examination revealed a schwannoma. We present this case as a rare manifestation of a schwannoma in hypothenar area of the hand. A literature review of diagnoses and therapeutic management is also presented.